Ultra-early endovascular treatment improves prognosis in High grade aneurysmal subarachnoid hemorrhage: A single-center retrospective study - Wu, Botao; Huang, Zhe; Liu, Huan; He, Jiayao; Ju, Yan; Chen, Ziwei; Zhang, Taiwei; Yi, Fuxin (Frontiers in Neurology, 2022)
Background: High-grade (Hunt-Hess grade IV-V or WFNS grade IV-V) aSAH (aneurysmal subarachnoid hemorrhage) generally is characterized by poor prognosis for long-term survival, and the association between endovascular treatment timing and the prognosis of High-grade aSAH have not been thoroughly explored. The aim of this retrospective cohort study is to determine whether ultra-early (within 24 hours) endovascular treatment of high-grade aSAH is associated with better prognosis. Methods: We retrospectively analyzed the clinical data of High-grade aSAH patients admitted in our institution from January 2018 to January 2021. Modified Rankin Scale scores were assessed the prognosis of patients at 6 months. Univariable and multivariable logistic regression analyses were used to identify factors associated with prognosis. The area under receiver operating characteristic curves (AUC) was used to assess the model’s discriminatory ability. Results: A total of 86 patients were included in the study. In multivariate regression analysis, the timing of endovascular treatment (OR=10.903 [2.489-47.769], P=0.002) was an independent risk factor for prognosis. The receiver operating characteristic (ROC) curve showed that the predictive power of the timing of endovascular treatment was 0.744, the best value of cut-off was 12.5 (h), and the corresponding sensitivity and specificity were 71.4% and 70.5%, respectively. At the same time, hydrocephalus(p=0.014), pulmonary infection(P=0.009), and length of hospital stay(P=0.002) were also associated with prognosis. In addition, cerebrospinal fluid drainage immediately after endovascular treatment has a significant effect on reducing the formation of hydrocephalus. Conclusions: Ultra-early endovascular therapy is feasible for patients with high-grade aneurysmal